Analysis of Poverty and Unemployment Reduction Strategies in the Highlands of North Sumatra by the North Sumatra Regional Development Planning Agency (Bappedasu) - Nadia Mayang Rukmana; Marliyah Marliyah (Jurnal Fokus Manajemen, 2022)
This study aims to determine the Strategy for Reducing Poverty and Unemployment in the Highlands of North Sumatra by the Regional Development Planning Agency of North Sumatra (Bappedasu) and to find out what factors hinder the performance of the Regional Development Planning Agency of North Sumatra in Reducing Poverty and Unemployment in the Plains Region. North Sumatra High. The North Sumatra Regional Development Planning Agency is an agency or government agency that aims to coordinate development in the North Sumatra area. This research was conducted at the North Sumatra Regional and Development Planning Agency (BAPPEDASU). This study uses qualitative research methods with the type of exploratory research with data collection techniques through observation, interviews, and documentation. In this study, a purposive sample strategy was utilized to recruit informants. With the results of the research that the Regional Development Planning Board of North Sumatra is still not as expected or has not carried out its overall task. This can be seen from the fact that the development target of North Sumatra Province in 2021 has not been achieved, especially in the highlands. And the factors that hinder the North Sumatra Regional Development Planning Agency are the rupiah exchange rate which shows an increase, the lack of job training centers, low public trust, the low rate of continuing schooling from high school / vocational school to university due to poor family conditions, and the spread of Covid19.